2018
DOI: 10.1007/s11250-018-1702-8
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic study of donkeys administered with Pycnogenol® and subjected to packing during the hot-dry season in Northern Nigeria

Abstract: The aim of the study was to determine some ergonomic parameters of donkeys administered with Pycnogenol® (PYC) and subjected to packing during the hot-dry season in northern Nigeria. Fifteen donkeys served as experimental subjects. Group 1 (n = 5) donkeys were subjected to trekking only (control), group 2 (n = 5) donkeys were subjected to packing (P-PYC), and group 3 (n = 5) were administered with PYC (10 mg/kg) and subjected to packing (P+PYC). Each group covered a distance of 10 km. Some ergonomic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The recorded response in the donkeys subjected to both packing and trekking was an adaptive mechanism to sustain the cardiac activities for a longer time and ensure its efficiency [ 26 ]. Based on the HR values, the findings of this study strongly suggest that packing + trekking was more stressful on the donkeys than trekking only [ 16 ], although the effects of both packing + trekking and trekking only were all abolished at least 16 hr after the packing and/or trekking period. This finding demonstrated that donkeys may be exposed to repeated packing without negative effects, at least at 16-hr intervals.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The recorded response in the donkeys subjected to both packing and trekking was an adaptive mechanism to sustain the cardiac activities for a longer time and ensure its efficiency [ 26 ]. Based on the HR values, the findings of this study strongly suggest that packing + trekking was more stressful on the donkeys than trekking only [ 16 ], although the effects of both packing + trekking and trekking only were all abolished at least 16 hr after the packing and/or trekking period. This finding demonstrated that donkeys may be exposed to repeated packing without negative effects, at least at 16-hr intervals.…”
Section: Discussionmentioning
confidence: 94%
“…The results for the RRs immediately after packing + trekking and trekking only show that packing + trekking and trekking only significantly increased the RRs of the donkeys; due to the adverse effects of the stress of packing and trekking on them. Trekking is a form of exercise in donkeys [ 16 ]. Thus, it exerted a significant impact on the donkeys in the hot-dry season by altering their respiration, as evidenced by the increase in their RRs recorded after packing and/or trekking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The poor performance of donkeys is mostly due to overworking, overloading and exposure to multiple stressors ( Ayo et al, 2013 ). Heat stress, caused by high ambient temperature (AT) and relative humidity (RH), has been reported to lead to reduction in performance in working animals ( Pal et al, 2002 ; Olaifa et al, 2019 ). Moderate stress has been reported in donkeys covering 9 km distance and carrying loads equivalent to the 50% of their body weight ( Pal et al, 2012 ; Legha et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in physiological parameters such as respiratory rate (RR) and heart rate (HR) have been used as indicator of stress in pack donkeys ( Ayo et al, 2008 , 2014 ; Legha et al, 2018 ; Frippiat et al, 2021 ). Increased HR in working donkeys during and after packing indicates physiological responses not only to the load carried, but also the ability of the animals to cope with stresses, generated by trekking over long distances and stressful meteorological parameters ( Olaifa et al, 2019 ). The balance between heat produced plus heat gain from the environment and heat loss in donkeys is enhanced by the adjustment of RR and HR ( Ayo et al, 2008 , 2014 ; Lacetera, 2019 ).…”
Section: Introductionmentioning
confidence: 99%